Integration of Strategic Management and Organizational Culture in Enhancing Corporate Resilience in the Digital Era - Loso Judijanto; Titis Sri Wulan; Otje Herman Wibowo; Rean Mitasari; Andreas Recki Prasetyo (SEULANGA SYSTEM PUBLISHER, 2025)
The rapid advancement of digital technology has transformed the global business landscape, presenting both opportunities and challenges for organizations. This study examines the integration of strategic management and organizational culture as a critical factor in enhancing corporate resilience in the digital era. Using a qualitative case study approach, data were collected from selected medium- and large-scale companies in Indonesia across diverse sectors, including manufacturing, technology, finance, and services. The findings reveal that strategic alignment between digital initiatives and cultural values significantly strengthens organizations’ adaptability to technological disruptions and market uncertainties. The study highlights the pivotal role of digital leadership in bridging strategic objectives with cultural practices. Leaders who promote innovation, collaboration, and flexibility were found to inspire employees to engage in continuous learning and proactive adaptation, thereby reinforcing resilience. Moreover, organizations with adaptive and innovation-driven cultures demonstrated greater capability in responding quickly to market changes and crises. Human resource practices aligned with cultural values further enhanced employee engagement and commitment, supporting the implementation of strategic initiatives effectively. In addition, the use of digital tools such as cloud-based systems and predictive analytics, combined with transparent communication with stakeholders, was identified as a key enabler of resilience. These tools not only improved operational efficiency but also strengthened stakeholder trust, ensuring continued support during uncertain times. Overall, the integration of strategic management and organizational culture, supported by digital leadership and technology, creates a comprehensive framework for building sustainable resilience. The study offers valuable insights and practical recommendations for organizations seeking to adapt and thrive in an increasingly dynamic and competitive digital business environment.